3 D Imaging and Structural Analysis of a Mesoporous‐Silica‐Body‐Supported Eggshell Cobalt Catalyst for Fischer–Tropsch Synthesis. Issue 18 (21st September 2016) - Han, Ting; Li, Xiaopeng; Lin, Chao; Zhang, Haojie; Gao, Peng; Zhao, Yonghui; Du, Fuping; Chen, Yuyun; Sun, Yuhan
Abstract: The front cover artwork for Issue 18/2016 is provided by Yuhan Sun's group at the Shanghai Advanced Research Institute, Chinese Academy of Sciences (SARI‐CAS) (P.R. China). The image shows a 3D full‐field view of the spatial distribution of active metal phases in a millimeter‐sized porous support. See the Full Paper itself at http://dx.doi.org/10.1002/cctc.201600657 . Abstract : "Seeing is believing" This and more about the story behind the research featured on the front cover can be found in this issue's Cover Profile. Read the full text of the corresponding research athttp://dx.doi.org/10.1002/cctc.201601107 .